Arbeitsgemeinschaft über auflösbare Gruppen: 23.4. bis 28.4. 1967 - Brandis, Albrecht; Huppert, Bertram (Tagungsbericht, 1967)
R. Berger, Berlin; A. Brandis, Heidelberg; B. Fischer, Frankfurt; W. Fischer, Göttingen; W. Gaschütz, Kiel; E. Gottschling, Berlin; F. Groß, Kiel; K. Höchsmann, Tübingen; B. Huppert, Mainz; W. Legrady, Hamburg; D. W. Müller, Erlangen; P. Roquette, Heidelberg; T. Yen, Kiel